2020
DOI: 10.1101/2020.10.23.352948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Life history tradeoffs, division of labor and evolutionary transitions in individuality

Abstract: Reproductive division of labor has been proposed to play a key role for evolutionary transitions in individuality (ETIs). This chapter provides a guide to a theoretical model that addresses the role of a tradeoff between life-history traits in selecting for a reproductive division of labor during the transition from unicellular to multicellular organisms. In particular, it focuses on the five keys assumptions of the model, namely (1) fitness is viability times fecundity; (2) collective traits are linear functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Grappling with the latter and recognizing that natural selection at the lower level cannot be invoked to explain the emergence of Darwinian properties at the higher level-doing so would assume that which requires explanation as the cause of its own evolution-led to development of the "ecological scaffolding" framework, which emphasizes the role of external factors in major evolutionary transitions (Figure 1 A E to D E ). This conceptual framework, which has both experimental [19][20][21] and theoretical [2,4,22] support, emphasizes that higher-level Darwinian properties can be exogenously imposed by specific ecological conditions.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Grappling with the latter and recognizing that natural selection at the lower level cannot be invoked to explain the emergence of Darwinian properties at the higher level-doing so would assume that which requires explanation as the cause of its own evolution-led to development of the "ecological scaffolding" framework, which emphasizes the role of external factors in major evolutionary transitions (Figure 1 A E to D E ). This conceptual framework, which has both experimental [19][20][21] and theoretical [2,4,22] support, emphasizes that higher-level Darwinian properties can be exogenously imposed by specific ecological conditions.…”
Section: Introductionmentioning
confidence: 98%
“…They do so by developing properties that make the ecological scaffold unnecessary for their maintenance. In the case of the evolution of multicellularity, the evolution of an extracellular matrix maintaining the cells together in the absence of a scaffold represents an example of endogenization (see [2][3][4]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This tradeoff between improving patch (group) fitness and decreasing cell growth rate has been interpreted through the lens of fitness decoupling (Michod and Roze, 1999;Michod and Nedelcu, 2003;Okasha, 2005Okasha, , 2008Rainey and De Monte, 2014;Hammerschmidt et al, 2014), alluding to the fact that after an ETI, the fitness of the higher level construct (the patch) is no longer a simple function of the fitness of the individual components (the cells). However, the underlying assumptions of the notion of fitness decoupling and related terms such as "fitness transfer" or "export of fitness" have been called into question (Doulcier et al, 2022). In particular, it has been shown that properly measured, that is, measured over the same set of events, the fitness of cells and patches are always equal (Shelton and Michod, 2014;Bourrat, 2015b,a;Black et al, 2020).…”
Section: Introductionmentioning
confidence: 99%